Nature’s Wit in Motion: Eco-Consciousness in Bryson’s ‘The Lost Continent’ - Sonam (International Journal of Ecology and Environmental Sciences, 2024)
Travelling is an art form – a fascinating one, indeed. The human history and civilisation can be perceived as a collection of travel narratives to different places. Since antiquity, man has travelled to explore places, culture, life and his own self. This paper aims to assess Bill Bryson’s travelogue, ‘The Lost Continent’ from the ecocritical point of view. The objectives are to examine the various ways through which ecological concerns are expressed by the author in his journey through the 38 states of USA. The author’s writing style including the frequent use of wit and humour to highlight the astronomically-increasing ecological crisis makes the narrative engaging and his concerns valid. To study these objectives, this paper uses the research methodology of eco-consciousness which not only aims at creating environmental awareness among people but also considers the socio- political implications of human activities on nature and mankind.